White-coat and masked hypertension diagnoses in chronic kidney disease patients - Pereira da Silva, Henrique [UNESP] (2020)
The purpose of this study was to analyze which 24-hour ambulatory blood pressure measurement (ABPM) parameters should be used on masked hypertension (MH) and white-coat hypertension (WCH) diagnoses in chronic kidney disease (CKD) patients. Non-dialysis CKD patients underwent 24-hour ABPM examination between 01/27/2004 and 02/16/2012. They were followed from the 24-hour ABPM to January/2014 in an observational study. The WCH definitions tested were as follows: (a) office blood pressure (BP) ≥ 140/90 mm Hg and daytime ABPM BP ≤ 135/85 mm Hg (old criterion); and (b) office BP ≥ 140/90 mm Hg and 24-hour ABPM BP ≤ 130/80 mm Hg, daytime ABPM BP ≤ 135/85 mm Hg, and nighttime ABPM BP ≤ 120/70 mm Hg (new criterion). The MH definitions tested were as follows: (a) office BP < 140/90 mm Hg and daytime ABPM BP > 135/85 mm Hg (old criterion); and (b) office BP < 140/90 mm Hg and 24-hour ABPM BP > 130/80 mm Hg or daytime ABPM BP > 135/85 mm Hg or nighttime ABPM BP > 120/70 mm Hg (new criterion). The two definitions' predictive capacity was compared, regarding both WCH and MH. Cardiovascular mortality was the primary and all-cause mortality was the secondary outcome. Cox regression was adjusted to the variables: glomerular filtration rate, age, diabetes mellitus, and active smoking. There were 367 patients studied. The old criterion (exclusive mean daytime ABPM BP) was the only to distinguish sustained hypertension from WCH (adjusted HR: 3.730; 95% CI: 1.068-13.029; P =.039), regarding all-cause mortality. Additionally, the old criterion was the only one to distinguish normotension and MH, regarding cardiovascular mortality (adjusted HR: 7.641; 95% CI: 1.277-45.738; P =.026). Therefore, WCH and MH definitions based exclusively on daytime ABPM BP values (old criterion) were able to better distinguish mortality in this studied CKD cohort.